PDTM-14. MiR-1253 IS A NOVEL TUMOR SUPPRESSOR GENE IN MEDULLOBLASTOMA. (5th November 2018) - Kanchan, Ranjana; Perumal, Naveen; Atri, Pranita; Thapa, Ishwor; Nasser, Mohd; Perry, Deborah; Batra, Surinder; Mahapatra, Sidharth
Abstract: Medulloblastoma (MB), the most common malignant pediatric brain tumor, is a leading cause of childhood related morbidity and mortality. Large-scale transcriptional profiling and mutational analyses have facilitated the stratification of medulloblastoma into four primary subgroups, i.e. SHH (sonic hedgehog), WNT (wingless), and non-SHH/WNT groups 3 and 4. The most frequent cytogenetic abnormality in medulloblastoma, i.e. i17q, distinguishes the non-SHH/WNT subgroup. Haploinsufficiency of 17p13.3 is reported in up to 50% of human MB cases. Included within this locus is miR-1253, which is exclusively expressed in the brain and an important regulator of bone morphogenic proteins that play a critical role in cerebellar development. Recently, two oncogenic targets of miR-1253, i.e. TGIF2 and ALX4, were identified in SHH medulloblastoma. Based upon these observations, we hypothesized that miR-1253 may be a putative tumor suppressor gene that undergoes epigenetic silencing in pediatric medulloblastoma. We first discovered reduced expression of miR-1253 in 24 pediatric medulloblastoma specimens and in 7 medulloblastoma cell lines. We then learned that miR-1253 silencing is accomplished via hypermethylation; expectedly, de-methylation of miR-1253, resulted in the recovery of expression with a subsequent decline in MB cell proliferation. MiR-1253 restoration was further concomitant with activation of apoptotic pathways and cell cycle arrest at G0 /G1 phase. Moreover, miR-1253 overexpression led to a reduction in cell proliferation, colony formation, migration and invasive potential of MB tumor cell lines. Using high throughput RNA sequencing analysis and luciferase reporter assay, we further identified several oncogenic targets of miR-1253, including CDK-6 and CD276. Taken together, these data strongly support a tumor suppressive role for miR-1253. This would be the first time such an effect has been attributed to miR-1253 in the context of medulloblastoma.